East Wind Breaks: Identification of Zhongguofeng Music as a Form of “Chinese Crossover” and “Hybrid Thinking” in Contemporary Mandopop - Fan, Li; Wei, Chow Ow; Fee, Lee Yok; Mahamed, Mastura; Nie, Connie Lim Keh (Universitas Negeri Semarang, 2024)
Since 2000, the phenomenal rise of Jay Chou, an iconic pop artist from Taiwan, has evoked discussions on Mandopop scene. This study aims to conduct a micro-analysis of selected music samples from Chou between 2000 and 2010 in order to identify Zhongguofeng music, which employs Phillip Tagg’s music analysis theory. The findings find out that Chou’s musical works demonstrate substantial Chinese elements in terms of lyrics, melody, and music cultural references. In addition, they reflect diversified musical styles, infusing Chinese-style hybridity into popular music. As a result, these musical works have formed a unique Zhongguofeng music standard that could play a defining role in contemporary Mandopop. It is anticipated that a discourse with a specific analytical setting could be established in this study. It can offer an insight into how the framework of hybridity in contemporary Mandopop is used to overcome the borders of genres, geopolitics, narratives, and negotiation of cultural identity between the “local” and the “global.”